Formaldehyde-free high-strength moisture-proof shaving board and preparation method thereof
Through the combination of modified isocyanate and nanocopper particles, the combination of magnesium glue adhesive and poplar wood shavings, the problems of formaldehyde release, mechanical properties and water absorption and expansion rate of particleboard are solved, and high strength and moisture resistance are improved.
Patent Information
- Application Number
- CN202411420337.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-31
AI Technical Summary
Existing particleboards have problems such as formaldehyde emission pollution, poor mechanical properties, insufficient bending resistance and high water absorption and expansion rate, which limits their application scenarios and moisture-proof performance.
Modified isocyanate as the adhesive for the surface material, and nano copper particles were added. The core material was made of poplar wood shavings and magnesium glue. It was prepared by combining corn stalks of different sizes and hot pressing. Formaldehyde-free high-strength moisture-proof particle board.
It significantly reduces the formaldehyde emission, improves the static curve strength and moisture-proof performance of particleboard, reduces the water absorption and expansion rate, and extends the application scenario.
Smart Images

Figure BDA0005080583680000031 
Figure BDA0005080583680000032 
Figure BDA0005080583680000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial boards, and in particular to a formaldehyde-free high-strength moisture-proof particle board and a preparation method thereof. Background Art
[0002] Particleboard is a man-made board made by cutting wood and other raw materials into pieces of certain specifications, drying them, mixing them with adhesives, additives, etc., and pressing them at a certain temperature. The raw materials of particleboard come from a wide range of sources, and the amount of glue used in the production process is small. The product has the characteristics of greater strength and higher stability, and has a very broad development space in my country.
[0003] The adhesives used for particleboard are mostly urea-formaldehyde resin glue and phenol-formaldehyde resin glue. The curing temperature of aldehyde adhesives is low, and they have good bonding effects on particleboards made of various plant materials such as wheat straw and rice husks. The hot pressing temperature is not high, so they are widely used in production. However, they have the disadvantage of releasing free formaldehyde to pollute the environment and endanger the health of users. At the same time, ordinary particleboard has poor physical and mechanical properties, low static bending strength, and its bending resistance decreases significantly after being subjected to pressure. Reinforcements are needed to assist in improving its bearing capacity. In addition, since the main material of particleboard is wood, it is easy to absorb water and moisture, which causes the compacted part inside the particleboard to expand and spread easily, causing damage to the entire particleboard.
[0004] Therefore, how to use formaldehyde-free raw materials to prepare particleboard, while improving the static bending strength of the particleboard during use, expanding the application scenarios, reducing the water absorption thickness expansion rate, and improving moisture-proof performance has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof. The present invention compounds corn straw shavings of the particleboard surface material with different sizes, selects modified isocyanate as the adhesive of the surface material, and adds nano copper particles as an additive. At the same time, the core material uses poplar shavings and is equipped with a magnesium adhesive. The prepared particleboard has extremely low formaldehyde emission, effectively improves the static bending strength of the particleboard when it is used, and reduces the water absorption thickness expansion rate, thereby obtaining a formaldehyde-free high-strength moisture-proof particleboard.
[0006] The first aspect of the present invention provides a method for preparing a formaldehyde-free high-strength moisture-proof particleboard, which is characterized by comprising the following preparation steps:
[0007] Step S1: preparing a surface material and a core material, wherein the surface material is corn stalk shavings, and the core material is poplar shavings;
[0008] Step S2: sizing the surface layer material and the core layer material described in step S1, uniformly mixing 90-100 parts of the surface layer material, 4-8 parts of the surface layer adhesive and 1-2 parts of the additive in a first mixer to obtain a sizing surface layer material, and uniformly mixing 90-95 parts of the core layer material and 5-10 parts of the core layer adhesive in a second mixer to obtain a sizing core layer material;
[0009] Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab;
[0010] Step S4: the slab described in step S3 is preheated and sent into a hot press to be hot-pressed and fixed to obtain a plate;
[0011] Step S5: cutting, cooling and sanding the board described in step S4 to prepare a formaldehyde-free, high-strength, moisture-proof particleboard.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the surface material in step S1 includes corn straw shavings I and corn straw shavings II; the mass ratio of corn straw shavings I and corn straw shavings II is 1:(0.5-1); the length of corn straw shavings I is 25-100 mm, and the width is 10-15 mm; the corn straw shavings II are broken corn straw shavings with a diameter of 2-6 mm.
[0014] Corn straw shavings I are larger in size and can serve as the main support of the particleboard, while the outer surface of corn straw shavings II is fully opened after crushing, so that the inner surface is exposed and the fiber separation is finer, resulting in a decrease in the proportion of the wax layer on the surface of the corn straw shavings to the total area. In addition, the crushed corn straw shavings II are small in size and easier to compress, which can fill the gaps in the corn straw shavings I, thereby improving the internal bonding strength and density value and reducing the water absorption thickness expansion rate of the particleboard.
[0015] As a preferred technical solution of the present invention, the surface adhesive in step S2 is a modified isocyanate adhesive; the modified isocyanate adhesive is selected from any one or a combination of at least two of modified isocyanate I, modified isocyanate II and modified isocyanate III;
[0016] Wherein, the structural formula of the modified isocyanate I is:
[0017]
[0018] Wherein, the structural formula of the modified isocyanate II is:
[0019]
[0020] Wherein, the structural formula of the modified isocyanate III is:
[0021]
[0022] Conventional isocyanate groups are highly reactive and can cross-link and solidify with compounds containing active hydrogen atoms such as alcohols, amines and water at room temperature. By modifying the isocyanate, the active isocyanate groups are blocked, which can remain stable at room temperature while avoiding water absorption and reducing the thickness expansion rate due to water absorption. Under high temperature conditions, the free isocyanate groups can be unblocked and released to fully react with the surface material corn straw shavings.
[0023] As a preferred technical solution of the present invention, the additive in step S2 is nano copper particles, and the size of the nano copper particles is 10-30nm. Nano copper particles have good thermal conductivity, and their high thermal conductivity enables them to effectively transfer heat. The good thermal conductivity allows the surface material to be heated evenly, which is more conducive to the reaction of the modified isocyanate, and the strength of the particleboard is improved by the full curing of the modified isocyanate adhesive; at the same time, the nano copper particles can be used as a medium to better transfer heat to the core layer material, and the magnesium adhesive in the core layer material contains magnesium chloride, which also has good thermal conductivity. By ensuring the thermal conductivity, the core layer reaction is fully achieved, and the strength of the particleboard is further improved.
[0024] As a preferred technical solution of the present invention, the core layer adhesive in step S2 is a magnesium adhesive; the magnesium adhesive is composed of magnesium oxide and magnesium chloride.
[0025] The preparation method of the magnesium adhesive comprises the following steps: weighing 2 to 4 parts of magnesium chloride and slowly adding it into distilled water to form brine, then adding 10 to 20 parts of magnesium oxide into the brine, stirring it with a stirrer for 3 to 5 minutes, and then placing it on a horizontal vibration table and vibrating it for 1 to 2 minutes to eliminate bubbles, so as to obtain the magnesium adhesive.
[0026] On the one hand, magnesium adhesive is scattered on the surface of poplar wood shavings, and bonding occurs through intermolecular hydrogen bonds, van der Waals forces, and the association of hydroxyl groups on the poplar cellulose molecular chain with hydroxyl groups in magnesium adhesive. At the same time, free Mg ions and Cl ions in magnesium adhesive react with poplar wood components to produce chemical bonds, thereby obtaining high strength for particleboard. On the other hand, magnesium adhesive can form crystals and hydration layer flocs, forming a good waterproof protective layer for poplar wood shavings, so that the pores in the wood shavings are filled and blocked by adhesives to a certain extent, and form a certain wrapping and barrier, making it difficult for moisture to enter, effectively improving the moisture-proof performance of particleboard.
[0027] Preferably, the temperature of the preheating section in step S4 is 50-60° C.; the hot pressing speed of the hot pressing section is 0.1-0.2 mm / s, the hot pressing temperature is 160-230° C., and the hot pressing plate surface pressure is 1.0-2.0 MPa.
[0028] The second aspect of the present invention provides a formaldehyde-free high-strength moisture-proof particleboard prepared by the method described in the first aspect.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention adopts modified isocyanate as adhesive for the surface layer material and magnesium adhesive for the core layer material to replace the traditional aldehyde-based adhesive, thereby effectively avoiding the appearance of formaldehyde and significantly reducing the formaldehyde emission, thereby obtaining a formaldehyde-free particleboard.
[0031] (2) The present invention compounds corn straw shavings of different sizes as the surface material of the particleboard. The small-sized crushed corn straw shavings II can fill the gaps of corn straw shavings I, thereby improving the internal bonding strength and density value and reducing the water absorption thickness expansion rate of the particleboard; and modified isocyanate is selected as the adhesive for the surface material. The modified isocyanate can remain stable at room temperature and avoid water absorption, thereby improving moisture resistance. (3) The present invention uses poplar shavings and magnesium adhesive as the core material. The free Mg ions and Cl ions in the magnesium adhesive react with the poplar components to form a coordination complex reaction, thereby improving the strength of the particleboard. At the same time, the magnesium adhesive can form crystals and hydration layer flocs to form a good waterproof protective layer, thereby reducing the water absorption thickness expansion rate. DETAILED DESCRIPTION
[0032] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0033] The sources of some components in the examples and comparative examples of the present invention are as follows:
[0034] Surface material: conventional corn straw shavings (purchased from Wanhua Jingzhou Company); corn straw shavings I and corn straw shavings II (prepared according to the method described in the paper "Experimental Study on the Effect of Shavings Morphology on the Performance of Straw Boards [J]. China Agricultural Mechanization, 2011 (3): 3 Wang Qi, Hu Xiaoli, Li Song, et al.").
[0035] Surface adhesive: isocyanate adhesive (brand CW20, purchased from Wanhua Chemical Group);
[0036] Additives: Nano copper particles (CAS No. 7440-50-8);
[0037] Core material: poplar wood shavings (purchased from Wanhua Jingzhou Company);
[0038] Core layer adhesive: phenolic adhesive (brand number 14L962, purchased from Aiketai New Materials Co., Ltd.).
[0039] Preparation of magnesium adhesive: Weigh 2 parts of magnesium chloride and slowly add it to distilled water to form brine, then add 10 parts of magnesium oxide to the brine, stir it with a stirrer for 3 to 5 minutes, then place it on a horizontal vibration table and vibrate it for 1 to 2 minutes to eliminate bubbles, so as to obtain magnesium adhesive.
[0040] Example 1
[0041] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof, the preparation method comprising the following steps:
[0042] Step S1: preparing 50 parts of corn straw shavings I (length 100 mm, width 15 mm) and 50 parts of corn straw shavings II (diameter 6 mm) as surface materials, and 90 parts of poplar wood shavings as core materials;
[0043] Step S2: sizing the surface layer material and the core layer material described in step S1, uniformly mixing 100 parts of the surface layer material, 8 parts of modified isocyanate I and 2 parts of nano copper particles (size of 30 nm) in a first mixer to obtain a sizing surface layer material, and uniformly mixing 90 parts of the core layer material and 10 parts of magnesium adhesive in a second mixer to obtain a sizing core layer material;
[0044] Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab;
[0045] Step S4: the slab described in step S3 is preheated and then sent into a hot press to be hot pressed and fixed to obtain a plate; wherein the temperature of the preheating section is 60°C, the hot pressing speed of the hot pressing section is 0.2mm / s, the hot pressing temperature is 230°C, and the hot pressing plate surface pressure is 2.0MPa;
[0046] Step S5: cutting, cooling and sanding the board described in step S4 to prepare a formaldehyde-free, high-strength, moisture-proof particleboard.
[0047] Example 2
[0048] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof, the preparation method comprising the following steps:
[0049] Step S1: preparing 60 parts of corn straw shavings I (length 25 mm, width 10 mm) and 30 parts of corn straw shavings II (diameter 2 mm) as surface materials, and 95 parts of poplar wood shavings as core materials;
[0050] Step S2: sizing the surface layer material and the core layer material described in step S1, uniformly mixing 90 parts of the surface layer material, 4 parts of modified isocyanate II and 1 part of nano copper particles (size of 10 nm) in a first mixer to obtain a sizing surface layer material, and uniformly mixing 95 parts of the core layer material and 5 parts of magnesium adhesive in a second mixer to obtain a sizing core layer material;
[0051] Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab;
[0052] Step S4: the slab described in step S3 is preheated and sent into a hot press to be hot pressed and fixed to obtain a plate; wherein the temperature of the preheating section is 50°C, the hot pressing speed of the hot pressing section is 0.1mm / s, the hot pressing temperature is 160°C, and the hot pressing plate surface pressure is 1.0MPa;
[0053] Step S5: cutting, cooling and sanding the board described in step S4 to prepare a formaldehyde-free, high-strength, moisture-proof particleboard.
[0054] Example 3
[0055] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof, the preparation method comprising the following steps:
[0056] Step S1: preparing 55 parts of corn straw shavings I (length 80 mm, width 12 mm) and 40 parts of corn straw shavings II (diameter 4 mm) as surface materials, and 92 parts of poplar wood shavings as core materials;
[0057] Step S2: sizing the surface layer material and the core layer material described in step S1, uniformly mixing 95 parts of the surface layer material, 6 parts of modified isocyanate III and 1.5 parts of nano copper particles (size of 18 nm) in a first mixer to obtain a sizing surface layer material, and uniformly mixing 92 parts of the core layer material and 8 parts of magnesium adhesive in a second mixer to obtain a sizing core layer material;
[0058] Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab;
[0059] Step S4: the slab described in step S3 is preheated and then sent into a hot press to be hot pressed and fixed to obtain a plate; wherein the temperature of the preheating section is 55°C, the hot pressing speed of the hot pressing section is 0.12mm / s, the hot pressing temperature is 210°C, and the hot pressing plate surface pressure is 1.4MPa;
[0060] Step S5: cutting, cooling and sanding the board described in step S4 to prepare a formaldehyde-free, high-strength, moisture-proof particleboard.
[0061] Example 4
[0062] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof. The only difference from Example 1 is that the surface material of this example is replaced with 100 portions of corn straw shavings (purchased from Wanhua Jingzhou Company), and the rest is the same as Example 1.
[0063] Example 5
[0064] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof. The only difference from Example 1 is that the surface adhesive in this embodiment is replaced with 8 parts of isocyanate adhesive (brand CW20, purchased from Wanhua Chemical Group), and the rest is the same as in Example 1.
[0065] Example 6
[0066] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof. The only difference from Example 1 is that this example does not contain 2 parts of nano copper particles, and the rest is the same as Example 1.
[0067] Example 7
[0068] This embodiment provides a formaldehyde-free high-strength moisture-proof particleboard and a preparation method thereof. The only difference from Example 1 is that the core layer adhesive is replaced with 10 parts of phenolic adhesive (brand 14L962, purchased from Aiketai New Materials Co., Ltd.) in this example, and the rest is the same as Example 1.
[0069] Comparative Example 1
[0070] This embodiment provides a particleboard and a preparation method thereof, the preparation method comprising the following steps:
[0071] Step S1: preparing 100 parts of corn stalk shavings (purchased from Wanhua Jingzhou Company) as surface material and 90 parts of poplar wood shavings as core material;
[0072] Step S2: Gluing the surface layer material and the core layer material described in step S1, mixing 100 parts of the surface layer material and 8 parts of isocyanate adhesive (brand CW20, purchased from Wanhua Chemical Group) were uniformly mixed to obtain a sizing surface material, and 90 parts of the core layer material and 10 parts of phenolic adhesive (brand 14L962, purchased from Aiketai New Materials Co., Ltd.) were uniformly mixed in a second mixer to obtain a sizing core layer material;
[0073] Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab;
[0074] Step S4: the slab described in step S3 is preheated and then sent into a hot press to be hot pressed and fixed to obtain a plate; wherein the temperature of the preheating section is 60°C, the hot pressing speed of the hot pressing section is 0.2mm / s, the hot pressing temperature is 230°C, and the hot pressing plate surface pressure is 2.0MPa;
[0075] Step S5: cutting, cooling and sanding the board in step S4 to prepare a particleboard.
[0076] The particleboards provided in the above embodiments and comparative examples were tested, and the specific testing methods are as follows:
[0077] Formaldehyde emission: Tested in accordance with the requirements of GB 18580-2017 Limits of formaldehyde emission from artificial boards and their products for interior decoration and renovation materials.
[0078] Static bending strength: Tested in accordance with the requirements of GB / T 4897-2015 Particleboard.
[0079] Water absorption thickness expansion rate: Tested in accordance with the requirements of GB / T 4897-2015 Particleboard.
[0080] The above performance test data is shown in Table 1:
[0081] Table 1
[0082]
[0083] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a formaldehyde-free high-strength moisture-proof particleboard, characterized in that: The preparation steps include: Step S1: preparing a surface material and a core material, wherein the surface material is corn stalk shavings, and the core material is poplar shavings; Step S2: sizing the surface layer material and the core layer material described in step S1, uniformly mixing 90-100 parts of the surface layer material, 4-8 parts of the surface layer adhesive and 1-2 parts of the additive in a first mixer to obtain a sizing surface layer material, and uniformly mixing 90-95 parts of the core layer material and 5-10 parts of the core layer adhesive in a second mixer to obtain a sizing core layer material; Step S3: paving the glued surface layer material and the glued core layer material described in step S2 to form a slab; Step S4: the slab described in step S3 is preheated and sent into a hot press to be hot-pressed and fixed to obtain a plate; Step S5: cutting, cooling and sanding the board described in step S4 to prepare a formaldehyde-free, high-strength, moisture-proof particleboard.
2. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 1, characterized in that: The surface material in step S1 includes corn straw shavings I and corn straw shavings II; the mass ratio of the corn straw shavings I and the corn straw shavings II is 1:(0.5-1); the length of the corn straw shavings I is 25-100 mm, and the width is 10-15 mm; the corn straw shavings II are broken corn straw shavings with a diameter of 2-6 mm.
3. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 1, characterized in that: The surface adhesive in step S2 is a modified isocyanate adhesive.
4. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 3, characterized in that: The modified isocyanate adhesive is selected from any one or a combination of at least two of modified isocyanate I, modified isocyanate II and modified isocyanate III; Wherein, the structural formula of the modified isocyanate I is: Wherein, the structural formula of the modified isocyanate II is: Wherein, the structural formula of the modified isocyanate III is:
5. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 1, characterized in that: The additive in step S2 is nano copper particles, and the size of the nano copper particles is 10-30 nm.
6. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 1, characterized in that: The core layer adhesive in step S2 is a magnesium adhesive.
7. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 6, characterized in that: The magnesium adhesive consists of magnesium oxide and magnesium chloride.
8. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 7, characterized in that: The preparation method of the magnesium adhesive comprises the following steps: weighing 2 to 4 parts of magnesium chloride and slowly adding it into distilled water to form brine, then adding 10 to 20 parts of magnesium oxide into the brine, stirring it with a stirrer for 3 to 5 minutes, and then placing it on a horizontal vibration table and vibrating it for 1 to 2 minutes to eliminate bubbles, so as to obtain the magnesium adhesive.
9. The method for preparing the formaldehyde-free high-strength moisture-proof particleboard according to claim 1, characterized in that: The temperature of the preheating section in step S4 is 50-60° C.; the hot pressing speed of the hot pressing section is 0.1-0.2 mm / s, the hot pressing temperature is 160-230° C., and the hot pressing plate surface pressure is 1.0-2.0 MPa.
10. A formaldehyde-free, high-strength, moisture-proof particleboard prepared according to the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Aldehyde-free liquid glue and artificial board processing method
CN105295740A
Chipboard and production method thereof
CN108162123A
Cited By
Fine-surface oriented strand board and preparation method thereof
CN120002785A
Formaldehyde-free moisture-proof medium-and-high-density straw artificial board and preparation method thereof
CN120190882A
